Market Power and Bank Liquidity Risk: Implementations of Basel III using Net Stable Funding Ratio Approach - Fadli, Jul Aidil; Sakti, Imanuel Madea; Jumono, Sapto (University of Merdeka Malang, 2021)
Net Stable Funding Ratio (NSFR) published by Basel III as a new standard of bank liquidity risk management. In Indonesia, the Financial Services Authority (OJK) issued the OJK Regulation No. 50/POJK. 03/2017 concerning the obligation to fulfill the NSFR for commercial banks. The research objective is to test the influence of bank market power of assets, loans, and third-party funds toward bank's liquidity risk that measured by NSFR. The research uses a data panel from 37 commercial banks in Indonesia in the period 2018Q1-2019Q4. The hypotheses are examined by using linear regression methods with a random effect model. The result shows that the effect of market power on the risk of bank liquidity is proved. Market power will increase the NSFR, which means the higher the market power, the better management of liquidity risk. This research is expected to contribute theoretically to provide the latest literature on the application of Basel III through the NSFR approach, a current measurement for bank liquidity risk. Furthermore, this research is expected to contribute practically to banks and regulators in the formulation of policies related to market control and bank liquidity risk management. Based on the result, financial consolidation to enhance market power can be a solution to encourage bank liquidity. DOI : https://doi.org/10.26905/jkdp.v25i2.5525